2021
DOI: 10.1109/access.2021.3132887
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Wearable Devices for Orientation and Mobility of Adults With Visual Impairment and Blindness

Abstract: Wearable devices have been developed to improve the navigation of blind and visually impaired people. With technological advancements, the use and research of wearable devices have been increasing. This systematic review aimed to explore existing literature on technologies used in wearable devices intended to provide independent and safe mobility for visually impaired people. Searches were conducted in six electronic databases (PubMed, Web of Science, Scopus, Cochrane, ACM Digital Library and SciELO). Our syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…The Smart Vision module utilizes GPS or Wi-Fi in indoor environments to provide regular and successive updates of the user’s geographic coordinates via the geographic information system and navigation modules [ 35 ]. When GPS or Wi-Fi signals are unavailable, RFID tags and computer vision are employed as supplementary technologies.…”
Section: Scientific Papersmentioning
confidence: 99%
“…The Smart Vision module utilizes GPS or Wi-Fi in indoor environments to provide regular and successive updates of the user’s geographic coordinates via the geographic information system and navigation modules [ 35 ]. When GPS or Wi-Fi signals are unavailable, RFID tags and computer vision are employed as supplementary technologies.…”
Section: Scientific Papersmentioning
confidence: 99%
“…To make the best use of these emerging technologies, it is valuable and timely to understand the state of this research and identify any shortcomings that are present. Previous reviews have highlighted a multitude of sensor-based technologies, ranging from smartphones ( Manjari et al., 2020 ) to VR headsets ( Htike et al., 2020 ; Aydmdoğan, Kavaklı, Şahin, Artal, & Ürey, 2021 ), which could be used to recognize commercial products ( Machado, Veras, Aires, & Britto Neto, 2021 ), detect obstacles and reduce navigation time ( Santos, Suzuki, Medola, & Vaezipour, 2021 ; Htike et al., 2020 ), or support social interactions ( Qiu et al., 2022 ). These articles also pointed to several gaps in the literature and suggested potential avenues for future research.…”
Section: Introductionmentioning
confidence: 99%
“…These articles also pointed to several gaps in the literature and suggested potential avenues for future research. On the technology side, some studies suggested to use smart clothing ( Santos et al., 2021 ) for nearby obstacle detection and to integrate devices with existing “Internet of Things” infrastructure ( Machado et al., 2021 ). On the behavioral side, Kelly and Smith (2011) lamented that most studies in their review lacked methodological rigor.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Electronic Travel Aids are based on sensors such as infrared, ultrasonic, Radio Frequency Identification (RFID), and G.P.S. to perceive the environment, process the information, and detect objects [ 4 ]. Further, many persons are unable to play video games because of visual impairments and have restricted accessibility while interacting with video games and taking part in various educational, social, and physical activities [ 5 ].…”
Section: Introductionmentioning
confidence: 99%